MANAGEMENT OF VATAKAPHAJA GRIDRASI WITH URDHWA SHODANA FOLLOWED BY BASTI-A CASE REPORT (AYUSHDHARA, 2020)
Gridrasi is one among the Vataja Nanatmaja Vyadhi with its one of the variant is Vatakaphaja. It’s Prathyatma Lakshana is Shoola radiating downwards from Sphik Pradesha upto Pada, which causes Nigraha of Sakthi Prasarana resulting in limping gait. Vata Kaphaja will present with Aruchi, Gourava along with above symptoms. Based on cardinal presentation it can be correlated to Sciatica, herniated lumbar disc being the most common cause with annual incidence of 0.5%-2%. In adults it is commonly seen in 3rd to 5th decade of life with male female ratio 2:1. The treatment protocol of Gridrasi includes Snehana, Swedana, Basti, Siravyadha and Agnikarma. Chakradatta emphasis on Urdhwashodana before administration of Basti. In this case Vatakaphaja Gridrasi initially treated with Snehana, Swedana line of treatment with no reduction in symptoms, responded very well to Basti administered after Urdhwa-shodana. Patient had significant reduction in symptoms and was able to perform his daily activities without pain.